2003
DOI: 10.1309/ych8dwuffqbkgpvb
|View full text |Cite
|
Sign up to set email alerts
|

The B-Cell Transcription Factors BSAP, Oct-2, and BOB.1 and the Pan–B-Cell Markers CD20, CD22, and CD79a Are Useful in the Differential Diagnosis of Classic Hodgkin Lymphoma

Abstract: Even with routine immunohistochemical evaluation, distinguishing classic Hodgkin lymphoma (CHL) from diffuse large B-cell lymphoma (DLBCL) or anaplastic large cell lymphoma (ALCL) can be difficult. In these cases, the transcription factors (B cell-specific activator protein [BSAP], octamer-binding transcription factor 2 [Oct-2], and B-cell Oct-binding protein 1 [BOB.1]) and the pan-B-cell markers (CD20, CD22, and CD79a) may aid in clarifying the diagnosis. In 57 cases of CHL, 5 cases of nodular lymphocyte pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
63
1
7

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 38 publications
14
63
1
7
Order By: Relevance
“…Similarly, OCT.1, OCT.2, and BOB.1 We did not find any significant association between OCT.1, OCT.2 and BOB.1 expression and the histological subtype, although the higher incidence of positivity of these markers in the lymphocyte-rich cases is notorious. This finding corroborates what previous studies have suggested about the fact that lymphocyte-rich classical Hodgkin's lymphoma might be more closely related to lymphocyte-predominant Hodgkin's lymphoma 30 than to the other classical subtypes or that it could be in between classical and lymphocyte-predominant Hodgkin's lymphoma. 33 From the 325 analysed cases, only a low percentage of them, less than expected, expressed CD20 and CD79a.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, OCT.1, OCT.2, and BOB.1 We did not find any significant association between OCT.1, OCT.2 and BOB.1 expression and the histological subtype, although the higher incidence of positivity of these markers in the lymphocyte-rich cases is notorious. This finding corroborates what previous studies have suggested about the fact that lymphocyte-rich classical Hodgkin's lymphoma might be more closely related to lymphocyte-predominant Hodgkin's lymphoma 30 than to the other classical subtypes or that it could be in between classical and lymphocyte-predominant Hodgkin's lymphoma. 33 From the 325 analysed cases, only a low percentage of them, less than expected, expressed CD20 and CD79a.…”
Section: Discussionsupporting
confidence: 92%
“…4,7,8,[28][29][30] In order to assess what previous studies have suggested about the lack of expression of transcription factors in classical Hodgkin's lymphoma, we performed an immunohistochemical analysis of OCT.1, OCT.2 and BOB.1 in 325 cases, using the tissue microarray technique and correlating the results to the histological subtype, B-cell marker expression, and Epstein-Barr virus presence. We decided to study the transcription factors on the neoplastic cells at Transcription factors in Hodgkin's lymphoma M García-Cosío et al the protein level because it might be more representative of their function than at the molecular level 28,31 and because there are few immunohistochemical studies including a large series of cases.…”
Section: Discussionmentioning
confidence: 99%
“…There is variation in the expression of these transcription factors reported in the literature due to small number of cases studied and/or to differences in immunohistochemical methods used. 9,10,22,23 We found a significant positive correlation between OCT.2 and CD79a expression (p=0.026), suggesting the existence of a common B-cell lineage down-regulating factor in H/RS cells. The latter observation was also made by Garcia-Cosio M et al 10 However, we did not find an association between BOB.1 and CD79a in our series.…”
Section: 1015mentioning
confidence: 63%
“…In the present study we analyzed the CD79a/ BCL6/MUM1 B-cell differentiation immunophenotypes and the B-cell transcription factors BOB.1/OCT.2 in H/RS cells in 107 cases of CHL aiming to elucidate the histogenesis of CHL and correlate the pattern of expression of these markers with clinical and laboratory characteristics and the patients' outcome. Most previous studies [8][9][10][11][12][13]22 have shown a variety of results regarding the expression of all these markers and furthermore their clinical significance is not clear.…”
mentioning
confidence: 99%
“…Typically, CHL shows weaker PAX5 expression in Hodgkin cells than in background B lymphocytes. 7,25,26 Several researchers have described a drastic loss of the B-cell-specific gene expression program in Hodgkin/Reed-Sternberg cells that may be related to downregulation of PAX5 mRNA. 27,28 This downregulation of gene expression most likely corresponds at the phenotypic level to decreased PAX5 protein expression and to less intense staining in tissue biopsies.…”
Section: Pax5 In Undifferentiated Neoplasmsmentioning
confidence: 99%